2022
DOI: 10.1111/jan.15375
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence: A cross‐sectional study among pregnant and postpartum women

Abstract: Methods:We interviewed women attending antenatal and postpartum care services in a Brazilian public tertiary woman's hospital in Campinas, São Paulo, between July 2019 and September 2021. Data were collected through interviewer-administered questionnaires previously used in healthcare settings: Abuse Assessment Screen (AAS); Woman Abuse Screening Tool (WAST); Hurt, Insulted, Threatened with Harm and Screamed (HITS). We evaluated the relationship between the sociodemographic characteristics of women and domesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 70 publications
1
8
0
1
Order By: Relevance
“…The study protocol 18 and the quantitative research 19 were published, and additional details about the research design, methods and results of the quantitative phase can be found in both publications.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study protocol 18 and the quantitative research 19 were published, and additional details about the research design, methods and results of the quantitative phase can be found in both publications.…”
Section: Methodsmentioning
confidence: 99%
“…The hospital where the research was conducted has a referral system installed for domestic violence survivors. It was established that those women who disclosed current domestic violence experiences must be offered social and psychological support from the regular hospital staff, as well as information about specialised services in their communities 19. The participants’ statements were identified with consecutive numerals to maintain anonymity.…”
Section: Ethics Statementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intimate partner violence (IPV) is a major public health issue and human rights threat worldwide [ 5 , 6 , 7 , 8 ]. The World Health Organization reported [ 9 ] that 27% of women aged 15–49 have experienced physical and/or sexual violence from their partners, and 13% of women have experienced such events in the past 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…Women are particularly vulnerable to violence from their partner during pregnancy and in the post‐partum period (Sánchez et al . 2022 ), and younger women are even more so (Woollett et al . 2022 ).…”
mentioning
confidence: 99%